Post-farmgate food businesses of India: The enterprises, the entrepreneurs, and the employees - Gupta, Manavi; Kishore, Avinash; Roy, Devesh; Saroj, Sunil (Elsevier, 2023)
In 2015–16, 21 million small and medium enterprises engaged in the business of manufacturing, trading, retailing, and serving food linked India's 146 million farmers to its nearly 1.3 billion consumers. These food enterprises employed 25 million men and 10 million women and had an annual turnover of $ 227 billion. Between 2010–11 and 2015–16, the gross value added (GVA) by the post-farmgate food businesses (PFFBs) increased by $16.3 billion (from $ 22.9 billion to $ 39.2 billion) which is comparable to the growth of $19.5 billion in the GVA by the primary food production (or the farm) sector which is nearly 10 times larger in size. Despite their growing contribution to the overall food economy, PFFBs are ignored in research and policy discussions on food systems. This paper tries to fill this gap by using two large nationally representative datasets from India—the Enterprise Survey and the Periodic Labor Force Survey (PLFS)—to assess the key characteristics of PFFBs and the entrepreneurs and employees who work in them. We show that despite rapid economic growth in the country, micro-enterprises with less than 5 employees continue to dominate India's food economy. Most of these firms are informal, rely purely on spot exchanges with their sellers and buyers, and do not borrow money from formal financial institutions. We find a strong positive association between the formal status and the productivity and profitability of PFFBs.